1996
DOI: 10.1007/3-540-61310-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Convexity and Steinitz's exchange property

Abstract: Abstract"Convex analysis" is developed for functions defined on integer lattice points. We investigate the class of functions which enjoy a variant of Steinitz's exchange property. It includes linear functions on matroids, valuations on matroids (in the sense of Dress and Wenzel), and separable concave functions on the integral base polytope of submodular systems. It is shown that a function ω has the Steinitz exchange property if and only if it can be extended to a concave function ω such that the maximizers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(121 citation statements)
references
References 20 publications
0
121
0
Order By: Relevance
“…In the most important case, M is the uniform matroid U d,n and P M is the hypersimplex ∆(d, n). Matroid subdivisions arose in algebraic geometry [HKT06,Kap93,Laf03], in the theory of valuated matroids [DW92,Mur96], and in tropical geometry [Spe08]. For instance, Lafforgue showed that if a matroid polytope P M has no nontrivial matroid subdivisions, then the matroid M has (up to trivial transformations) only finitely many realizations over a fixed field F. This is one of very few results about realizability of matroids over arbitrary fields.…”
Section: Matroid Subdivisions Valuations and The Derksen-fink Invarmentioning
confidence: 99%
“…In the most important case, M is the uniform matroid U d,n and P M is the hypersimplex ∆(d, n). Matroid subdivisions arose in algebraic geometry [HKT06,Kap93,Laf03], in the theory of valuated matroids [DW92,Mur96], and in tropical geometry [Spe08]. For instance, Lafforgue showed that if a matroid polytope P M has no nontrivial matroid subdivisions, then the matroid M has (up to trivial transformations) only finitely many realizations over a fixed field F. This is one of very few results about realizability of matroids over arbitrary fields.…”
Section: Matroid Subdivisions Valuations and The Derksen-fink Invarmentioning
confidence: 99%
“…Many other general classes of polyhedra with somewhat esoteric definitions have been studied: e.g. lattice polyhedra [17], submodular flow polyhedra [8], bisubmodular polyhedra [26, §49.11d], and M -convex functions [18]. In some cases the definitions are chosen to be precisely as general as possible while allowing the proof techniques to go through, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…where 0 ∈ E and y(E) denotes the sum of all the components of y. Functionf is called an M-concave function (Murota [18,19]). LetẼ = {0} ∪ E. For each vector x ∈ R E we denote byx the vector (−x(E), x) ∈ RẼ, and we write vectors in RẼ by putting tildes such asp andỹ (e.g.,χ e is the characteristic vector of e onẼ).…”
Section: A Proof Of Theorem 35mentioning
confidence: 99%
“…LetẼ = {0} ∪ E. For each vector x ∈ R E we denote byx the vector (−x(E), x) ∈ RẼ, and we write vectors in RẼ by putting tildes such asp andỹ (e.g.,χ e is the characteristic vector of e onẼ). An M-convex function can be characterized by the following exchange property (Murota [18,19]):…”
Section: A Proof Of Theorem 35mentioning
confidence: 99%
See 1 more Smart Citation